Indian stamp act, 1899 (New Delhi, 2015)
To raise revenue the British Government adopted a fiscal measure by enacting the Stamp Act, 1869 (18 of 1869) which was replaced by the Indian Stamp Act, 1879 (1 of 1879). Since the passing of the Act of 1879 the Stamp law was amended by ten different enactments. Inspite of that need was felt to enact a more comprehensive law. Accordingly the Indian Stamp Bill was introduced in the Legislature. The Bill was referred to the Select Committee. On the recommendations of the Select Committee changes were made in the Bill.
Keywords: Stamp act-India